To investigate the possibility of threshing pepper spikes and removing of pepper skin by mechanical mean - Dakek, Ijen (University Malaysia Sarawak (UNIMAS), 2000)
In this thesis, the threshing of pepper spikes and the deskining pepper berries using a mechanised system was performed and the effect of varying the speed on the quality of thresh and deskining, in term of effectiveness is discussed.